The Impact of the Communication Process on the Organizational Change Management: Empirical Evidence from SONATRACH Company Using PLS-SEM Approach - Yousfat, Ali; Mostéfaoui, Sofiane (Technium Social Sciences Journal, 2022)
This paper explores the crucial role of communication during the implementation of a new remuneration system at Sonatrach Company. The issue focuses on determining how the communication process plays a pivotal role in advancing establishment of NSR based on performance and efficiency. The study adopts the Structural Equation Modeling PLS-SEM methodology and the model comprises three latent variables (Communication, Managers’ Role and Resistance) and 16 indicators. The results show that the communication process impacts positively the organizational resistance while the managers’ role effect is negative.